A review Study of The Chemical Constituents and Pharmacological Activities of Alstonia scholaris linn - Majid, Alyaa; Faraj, Hadeel Rashid (University of Thi-Qar Journal of Science, 2023)
The Indian medical systems hold promise for the genus Alstonia. Different types of Alstonia, primarily Alstonia scholaris, have been used by the various ethnic communities in India to treat various human illnesses. A historically significant medicinal herb is Alstonia scholaris. The Indian subcontinent and Southeast Asian nations are the native habitats of this evergreen tree. The plant is used in conventional, Ayurveda, Unani, homoeopathic, Sidhha/Tamil, and other alternative medical systems to treat a variety of illnesses, including asthma, malaria, fever, dysentery, diarrhea, epilepsy, skin conditions, and snakebites, among others. Alkaloids make up the majority of reported phytochemicals. In this review, reports on pharmacological and phytochemical varieties of A. scholaris are compiled.